Efficacy of targeted drugs for the treatment of adults with moderate-to-severe plaque psoriasis in the Russian Federation: a systematic literature review update - V. D. Sokolova; N. A. Sableva; V. V. Mladov; D. G. Tolkacheva (Фармакоэкономика)
Background. A systematic literature review helps to identify the main treatment options, and evidence synthesis supports decision-making by comparing clinical efficacy of different treatments. Nowadays new drugs and clinical trials emerge rapidly, so previous network meta-analyses might need to be updated.Objective: to update the existing systematic review and network meta-analysis comparing efficacy of targeted drugs in adult patients with moderate-to-severe plaque psoriasis by adding randomized clinical trials (RCTs) on a new interleukin (IL) 23 inhibitor registered in the Russian Federation – risankizumab, and other RCTs published after 2019; to reassess the Psoriasis Area and Severity Index (PASI) 75/90 numbers of patients needed to treat to achieve clinical response to therapy and the costs per responder for 12–16 weeks and 1 year of therapy.Material and methods. We updated our systematic literature search in the PubMed/MEDLINE and Embase databases. Evidence synthesis included RCTs evaluating the efficacy of adalimumab (ADA), infliximab (INF), etanercept (ETN), certolizumab pegol (CZP), ixekizumab (IXE), netakimab (NTK), secukinumab (SEC), risankizumab (RIS), guselkumab (GUS), ustekinumab (UST), tofacitinib (TOFA), and apremilast (APR) after 12 weeks of therapy. The Bayesian meta-analyses with meta-regression models were performed in order to account for high heterogeneity in patient characteristics and significant differences in the placebo response rates. The considered drugs were ranked based on values of surface under the cumulative ranking curve (SUCRA). Additionally, drug class analyses were carried out.Results. Twenty three new RCTs were added to the network. IL-23 inhibitor RIS, recently approved in the Russian Federation, has joined the group of the most efficacious drugs, such as IL-17 inhibitors NTK and IXE, as well as IL-23 inhibitor GUS. In terms of PASI 75, RIS and IXE showed superiority compared to all tumor necrosis factor alpha (TNFα) inhibitors (INF, ADA, ETN), small molecules (TOFA and APR), and IL-12/23 inhibitor UST, while NTK and GUS were characterized by comparable efficacy with INF and outperformed the remaining drugs. There were no statistically significant differences in efficacy between all the TNFα inhibitors. GUS, IXE, INF, NTK, RIS and SEC demonstrated that no more than 2 patients need to be treated to achieve one PASI 75 response, and no more than 3 need to be treated for one PASI 90 response (according to the upper limit of 95% credible interval). Same as in the previously published study, NTK showed the lowest costs per responder for both 12-week and 1-year periods.Conclusion. The addition of head-to-head trials and increased statistical power of the network revealed previously unidentified significant differences between treatment options for moderate-to-severe plaque psoriasis.